2017
DOI: 10.2174/1871530316666161130160809
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Overweight and Obesity in Patients with Pituitary Dysfunctions

Abstract: In conclusion, we showed that patients with HPD: (i) frequently suffer from overweight and obesity; (ii) prevalence of overweight and obesity however is comparable to that in the general population; (iii) only patients with macroadenomas seem to have a significantly higher risk; (iv) hormone deficiencies and hormonal replacement therapy may foster weight gain and (v) radiation and surgical tumour therapy per se do not seem to be additional risk factors for weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It has already been observed that more often patients with macroadenomas are significantly overweight and obese than individuals with microadenomas. [26] Perhaps this finding may explain the higher frequency of obesity in acromegalics in this series, 94.1% of them with macroadenomas, in relation to individuals with Cushing's disease, 60% with macroadenomas.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has already been observed that more often patients with macroadenomas are significantly overweight and obese than individuals with microadenomas. [26] Perhaps this finding may explain the higher frequency of obesity in acromegalics in this series, 94.1% of them with macroadenomas, in relation to individuals with Cushing's disease, 60% with macroadenomas.…”
Section: Discussionmentioning
confidence: 73%
“…Schmid et al[25] investigated 399 adenomas and found that 22.2% of patients with Cushing's disease, 21.4% of patients with acromegaly, and 17% of patients with clinically nonfunctioning adenomas were obese. Harbeck et al[26] observed a higher prevalence of BMI ≥25 in prolactinomas (70%). In the present study, a higher percentage of obesity was found in patients with acromegaly (46.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as Harbeck et al report [21], apparently, body weight is not in uenced by hormonal activity in PA patients, since both individual with hormone secreting tumors and controls suffer from overweight or obesity. This was con rmed by our results, where we did not nd differences in weight between PA types.…”
Section: Surgery Success Strati Cation Outcomesmentioning
confidence: 94%
“…Only a few reports mention similar ndings, for example, Cheng et al reported that PA invasiveness or size did not associate proportionally with abnormal glucose metabolism [20]. Moreover, Harbeck and colleagues only report differential prevalence of overweight and obesity between patients with macro and microadenomas, with a higher prevalence in individuals with macroadenomas [21].…”
Section: Surgery Success Strati Cation Outcomesmentioning
confidence: 96%
“…The young female cased associated obesity and macroprolactinoma. Some studies pointed out that the patients with prolactin producing macroadenomas have a higher risk of obesity (independent of features related to central hypogonadism), but it is not a general observation (10,11).…”
Section: Prolactinoma and Obesitymentioning
confidence: 99%